Tariff Concessions in Production Sourcing - GUO, Yunsong (Institutional Knowledge at Singapore Management University, 2008)
In this paper, we study a multi-stage production sourcing problem where tariff concessions can be exploited at the firm level using free trade agreements between countries. To solve the problem, an algorithm which embeds a very large-scale neighborhood (VSLN) search into a simulated annealing framework is developed. A numerical study is conducted to verify the effectiveness of the solution approach.